PRODUKSI, KOMPOSISI BOTANI DAN KAPASITAS TAMPUNG HIJAUAN PADA PADANG PENGGEMBALAAN ALAM AWAL MUSIM KEMARAU (Production, botanical composition and carrying capacity of forage in native grassland at early dry season) - Ventryan Haryanto Hae; Markus Miten Kleden; Stefanus Tany Temu (JURNAL NUKLEUS PETERNAKAN, 2020)
Grassland area must be managed and record existing condition doe to as a source of cheapest feed and easy to find out. The aim of this study was to measure production, botanical composition and carrying capacity of forage in native grassland area at early dry season. This study was carried out in Maubokul village, Pandawai sub district, district of East Sumba. Forage production measured by actual weight estimate method with 1m x 1m of frame as tool utilization. Data collected than analyzed to find out production, botanical composition and carrying capacity of forage in native grassland. Statistical analysis showed that the value of Summed Dominance Ratio (SDR) was 84.4% for grass, 15.6% for legume and 0% for weeds. Dry matter production was 1.866,8 kg/ha with carrying capacity value was 1.05AU/Ha/year. As a conclusion that grassland area at Maubokul village was dominated of grass and carrying capacity was high.